PENGETAHUAN DAN PERSEPSI MAHASISWA TENTANG KESEHATAN REPRODUKSI DAN PERMASALAHANNYA - Kartika Ratna Pertiwi; Das Salirawati (LPPM UNY, 2014)
The aims of this research are to describe the knowledge level and perception accuracy toward reproductive health among students from Yogyakarta State University (YSU). This research was an analytical survey, with crosssectional approach. Population were YSU students while respondents were taken by simple random sampling. The instruments were adapted from Pertiwi (2007) which consist of questionnaires on knowledge about reproductive health and perception towards myths around sexual health problems. Data were analysed descriptively to determine the factors involved. There were 177 males and 174 female with an average age 20 years old. The highest and the lowest knowledge score were FMIPA and FBS respectively whereas the highest and the lowest perception score were FMIPA and FIK resepctively. Factors involved in knowledge were faculty origin, sex and socioeconomic status